ANALISA CASH RATIO DAN CURRENT RATIO MENURUT PERATURAN MENTERI USAHA KECIL DAN MENENGAH REPUBLIK INDONESIA - Amin Setio Lestiningsih (Universitas Bina Sarana Informatika, 2015)
LKMS is a financial institution that focuses on financing where the practice of usury is eliminated and the financial management and sharia-based operational. Financial statement analysis technique used is the analysis of liquidity. The ratio of liquidity analysis obtained, then be compared with existing scores in Regulation of the Minister of Cooperatives and Small and Medium Enterprises of the Republic of Indonesia Number : 20/Per/M.KUKM/XI/2008 dated 14 November 2008. Methods used in the form of descriptive methods qualitative. Cash Ratio Discussion Results obtained in 2011 and 2012 by 112 % and 116 % where the ratio of the two numbers indicate the criteria of less healthy because in between 100 % to 125 %, so that the position of the cash ratio becomes illiquid. Then in 2013 showed the ratio is 132 % healthy enough, which is located in the ratio between 125 % to 150 % so that the position of the cash ratio becomes liquid. CR in 2011, 2012 and 2013 amounted to 875 %, 503 %, 855 %, where the three ratios were above the standard ratio determined by the Ministry of Cooperatives and SMEs RI that is more than 175 % then it is highly illiquid in debt smooth. Based on the results of these discussions, the authors provide suggestions to improve the cash to increase revenue outside of savings. Keywords: Cash Ratio, Current Ratio, Micro Islamic Financial Institutions